BS EN 63184. Basic standard for the assessment of the human exposure to electric and magnetic fields from wireless power transfer systems. models, instrumentation, numerical methods and procedures (Frequency range of 1 kHz to 10 MHz). (5th September 2022) - British Standards Institution,
No abstract available